The effect of arm support and control modes on muscle fatigue, eye fatigue, and posture changes in mobile game use among young adults. Issue 5 (5th April 2021) - Guo, Fu; Liu, Li; Li, Mingming; Greene, Runyu L.
Abstract: Background: The popularity of mobile gaming among adults has raised concerns about the adverse health effects of localized muscle and eye fatigue. This study aimed to investigate how arm support and mobile game control characteristics affect muscle and eye fatigue, and postural changes. Methods: Twelve subjects, ages 21–24 years old, were recruited to play a mobile game for 60 min. Participants used two postures (sitting with and without arm support) and two game control modes (touch and rocker). Electromyography measured the abductor pollicis brevis, the upper trapezius, and the extensor carpi radialis muscles. A motion capture system was employed to assess postural changes. Self‐reported fatigue was measured using Borg's scale and Heuer's questionnaire. Results: Arm support had a significant effect on muscle fatigue and posture, including a lower rating of perceived exertion in the shoulder ( p  < .05) and arm ( p  < .01), an increase in neck and trunk forward flexion between 22% and 34%, an increase in forearm bearing angle of 97.63%, and a decrease in upper arm bearing angle of 25.94% in the group without arm support. Blink for touch mode was 10.57% higher than for rocker mode. Conclusion: Arm support was effective in reducing fatigue in the arm and shoulder, but not in the hand. Compared to rocker mode, touch mode increased the visual burden and accelerated visual fatigue. This study provides an understanding of the association between playing mobile games and fatigue, which can help prevent muscle and visual fatigue in mobile gaming.